2018
DOI: 10.2147/ott.s157638
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA-ROR promotes metastasis and invasion of esophageal squamous cell carcinoma by regulating miR-145/FSCN1

Abstract: Background and objectiveIn an attempt to discover a new biomarker for early diagnosis and prognosis of esophageal squamous cell carcinoma (ESCC), the regulation mechanism of large intergenic non-coding RNA–regulator of reprogramming (lincRNA-ROR) as a microRNA (miRNA) sponge was studied.Patients and methodsROR expression in 91 pairs of ESCC tissue samples and matched adjacent tissues was quantified with real-time fluorescent quantitative polymerase chain reaction (qRT-PCR). The ROR–miRNA–mRNA regulatory networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…The lncRNAs act as miRNAs sponges or inhibitors to suppress the interactions between miRNAs and target mRNAs [12]. The lncRNA-miRNA-mRNA regulatory network is suggested to play critical role in cancer tumourigenesis and progression [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs act as miRNAs sponges or inhibitors to suppress the interactions between miRNAs and target mRNAs [12]. The lncRNA-miRNA-mRNA regulatory network is suggested to play critical role in cancer tumourigenesis and progression [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The regulator of reprogramming (ROR, LncRNA-ROR) is a 2.6 kb long RNA comprised of four exons (Loewer et al 2010). Studies have shown that LncRNA-ROR is significantly up-regulated in induced pluripotent stem cells (iPSCs) (Loewer et al 2010), human embryonic stem cell (hESC) (Cheng and Lin 2013), and multiple cancer cells (Jiang et al 2016;Wang et al 2016aWang et al , 2016bArunkumar et al 2017;Chen et al 2017;Li et al 2017b, Liu et al 2017, Qu et al 2017, Shang et al 2018 including esophageal squamous, prostate cancer, breast cancer, pancreatic cancer, oral cancer. Research has Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…ROC analysis was performed to assess the feasibility of using miR‐25 levels as an early diagnostic tool in ESCC . The other significant biomarkers for the early diagnosis of ESCC are large intergenic noncoding RNA–regulator of reprogramming (lincRNA‐ROR) and miR‐367 . LincRNA‐ROR expression in 91 pairs of ESCC tissue samples and matched adjacent tissues was quantified with qRT‐PCR and a significantly higher expression of lincRNA‐ROR in ESCC tumor tissues than in the adjacent tissues was observed.…”
Section: Biomarkers In Oscc and Esccmentioning
confidence: 99%